ANALISA PENGENDALIAN MUTU PROYEK GUDANG PT SANTOS JAYA ABADI MENGGUNAKAN PROCESS DECISION PROGRAM CHART METHOD - Yohanes Usman Nandyanto; Michella Beatrix; Masca Indra Triana (Institut Teknologi Adhi Tama Surabaya, 2023)
Construction projects are growing wider and more complex in terms of physical and cost. In practice, a project has limited resources in people, materials, costs, or tools. Construction project must have quality control to guatantee safety worker. However, even though technical specifications have been prepared, deviations in quality during construction project implementation always occur, so that the quality of the resulting building does not comply with the quality requirements that have been set and causes the low quality of human resources in the construction world Factors causing quality control in this study can directly or indirectly affect the project. This research began with data collection through the process decision program chart method and questionnaire method, distributed to project warehouse PT Santos Jaya Abadi, with the respondents from project managers to workers. Furthermore, the collected data questionnaires were analyzed using the IBM SPSS dan Microsoft Excel. The analysis quality control and analysis risk show that quality control have a effective and well implemented in project contruction, with the result in structure work such as beam work and column work have the same percentage of 76% and floor plate work has a percentage of 72%. While on structure work such as beam has risk level value 7.49, column structure work with a value of 7.42, floor plate structure work with a value of 6.43.